Loxa Deducta Walker, 1867 (Heteroptera: Pentatomidae) in Chile: Distribution, history of invasion and identification Loxa Deducta Walker, 1867 (Heteroptera: pentatomidae) en Chile: distribución, historia de invasión e identificación - Faúndez, Eduardo I.; Rocca, Javiera R. (My University, 2018)
The presence of the introduced stink bug Loxa deducta Walker, 1867 in Chile is analyzed. New records are provided for the Valparaíso, O´Higgins and Maule regions, extending its distribution southwards and northwards. Identification tips are provided to differentiate it from other Chilean pentatomids, as well as Loxa Amyot & Serville, 1843 species in the neighbor countries.
Keywords: chile; faunistics; hemiptera; invasive species